First Report of Rhizome Rot Caused by Pectobacterium aroidearum on Ginger in China - Zhang, Aijing; Zuo, Lirong; Zhu, Lin; Wang, Jianfei; Zhou, Cheng (Plant disease, 2024)
Ginger (Zingiber officinale) is a vital commercial crop in China, valued for its medicinal and nutritional properties. From June to September 2023, soft rot symptoms were observed on ginger rhizomes in fields in Shucheng County, Lu'an City, Anhui Province, China (31°24'N, 116°53'E). Brown, water-soaked lesions emerged at the stem base, accompanied by leaf yellowing and wilting. Approximately 20% of the ginger fields in this region (about 530 hectares) displayed soft rot symptoms. Rhizomes from ten randomly diseased ginger plants from three different locations were surface disinfected (Liu et al. 2020). The disinfected rhizomes were ground in sterile water, and serial dilutions of the supernatant were then placed on Luria-Bertani (LB) agar, resulting in the isolation and purification of 432 colonies. Using the primer set 27F/1492R (Weisburg et al. 1991), the 16S rRNA gene was amplified and sequenced. BLASTn analysis indicated that Pectobacterium species were isolated from all three locations, accounting for one-fifth of the total isolates. Three isolates, PA03, PA05, and PA08, were randomly chosen for further analysis. These colonies appeared milky white, round, with a smooth surface and smooth margins. All three isolates were Gram-negative, tested negative for methyl red and catalase, but positive for urease. The 16S rRNA sequences obtained (GenBank accession No. PP935462, PP935465 and PP935466) were 100% identical to Pectobacterium aroidearum strains KNUB-05-21 (LC777355, 1,375/1,375 bp), 3898C (KY446053, 1,418/1,418 bp), and MY11 (MT834965, 1,373/1,373 bp). The icdA, mdh, and proA genes of the isolates were amplified by PCR using specific primer pairs icdA-F/icdA-R, mdh-F/mdh-R, and proA-F/proA-R, respectively (Ma et al. 2007). BLASTn searches showed that the icdA (PP922142), mdh (PP922148), and proA (PP922145) sequences of PA03 had similarities of 99.25%, 98.26%, and 98.01%, respectively, with those of P. aroidearum strain UNEB3 (MH500095, 563/536 bp; MH507329, 522/394 bp; MH507331, 655/702 bp). Similarly, the icdA (PP922143), mdh (PP922149), and proA (PP922146) sequences of PA05 were 99.05%, 99.09%, and 97.18% identical to those of P. aroidearum strain MTL1911110204 (MT013063, 529/552 bp; MT013079, 498/399 bp; MT013095, 717/714 bp). The icdA (PP922144), mdh (PP922150), and proA (PP922147) sequences of PA08 shared 99.25%, 98.27%, and 97.94% similarity with those of P. aroidearum strain CCRM35 (MH500096, 537/537 bp; MH507330, 513/396 bp; MH507332, 630/705 bp). Phylogenetic trees were generated using MEGA11.0 software based on 16S rRNA and concatenated sequences of icdA-mdh-proA (Tamura et al. 2021). The results of phylogentic analysis revealed that the isolates, PA03, PA05, and PA08, clustered with P. aroidearum strains. To test pathogenicity, 10 µl of bacterial suspensions (1×108 CFU/ml) of isolates PA03, PA05, and PA08 were inoculated into the stem base of ginger plants using a sterile syringe, with sterile water used as a control. Each isolate was inoculated into five pots, with three plants per pot. The plants were maintained in a greenhouse at 28°C with 75% relative humidity. Rhizomes inoculated with bacterial suspensions displayed soft rot symptoms resembling those observed in the field seven days after inoculation, while the control group remained free of symptoms. Bacteria were re-isolated from diseased tissues and identified by PCR with specific primer pairs icdA-F/icdA-R, mdh-F/mdh-R, and proA-F/proA-R. The re-isolated strains had the identical sequences as PA03, PA05, and PA08, confirming their pathogenicity and fulfilling Koch's postulates. P. aroidearum is known to cause soft rot in various crops (Barroso et al. 2019; Morase et al. 2020; Tang et al. 2021). To our knowledge, this is the first report of P. aroidearum causing soft rot disease of ginger rhizomes in China. In 2023, soft rot disease led to a 15 to 20% reduction in ginger yield, posing a substantial risk to ginger cultivation in Lu'an city. Identifying this pathogen is crucial for preventing disease outbreaks and developing effective disease management strategies.